2000
DOI: 10.1037/0278-7393.26.5.1198
|View full text |Cite
|
Sign up to set email alerts
|

Repetition priming for familiar and unfamiliar faces in a sex-judgment task: Evidence for a common route for the processing of sex and identity.

Abstract: Repetition priming for faces was examined in a sex-judgment task given at test. Priming was found for edited, hair-removed photos of unfamiliar and familiar faces after a single presentation at study. Priming was also observed for the edited photos when study and test faces were different exemplars. Priming was not observed, however, when sex judgments were made at test to photos of complete, hair-included faces. These findings were interpreted by assuming that, for edited faces, internal features are attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
147
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(179 citation statements)
references
References 78 publications
30
147
2
Order By: Relevance
“…Many studies of familiar faces have shown that priming decreases when the study and test stimuli differ because of a change of viewpoint (e.g., Bruce & Valentine, 1985;Ellis, Young, Flude, & Hay, 1987) or picture format (Bruce, Burton, Carson, Hanna, & Mason, 1994). A reduction in priming with viewpoint changes between study and test has also been found for unfamiliar faces (e.g., Goshen-Gottstein & Ganel, 2000), although one study reported a similar amount of reaction time facilitation from identical and changed-viewpoint pictures across multiple repeated presentations (Hay, 2000). This exception aside, pose changes between study and test may account for some failures to find evidence of priming for unfamiliar faces (e.g., Campbell & DeHaan, 1998).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Many studies of familiar faces have shown that priming decreases when the study and test stimuli differ because of a change of viewpoint (e.g., Bruce & Valentine, 1985;Ellis, Young, Flude, & Hay, 1987) or picture format (Bruce, Burton, Carson, Hanna, & Mason, 1994). A reduction in priming with viewpoint changes between study and test has also been found for unfamiliar faces (e.g., Goshen-Gottstein & Ganel, 2000), although one study reported a similar amount of reaction time facilitation from identical and changed-viewpoint pictures across multiple repeated presentations (Hay, 2000). This exception aside, pose changes between study and test may account for some failures to find evidence of priming for unfamiliar faces (e.g., Campbell & DeHaan, 1998).…”
mentioning
confidence: 80%
“…With tasks such as familiarity decision or naming of familiar faces, long-term repetition priming is strong (e.g., Bruce & Valentine, 1985;Ellis, Young, & Flude, 1990). However, with unfamiliar faces, for which the range of tasks is more restricted, much less repetition priming, if any, is found (e.g., Ellis et al, 1990;Goshen-Gottstein & Ganel, 2000). One theoretically important manipulation is to vary the face pictures between study and test.…”
mentioning
confidence: 99%
“…Moreover, category-relevant features (e.g., hair, which is a reliable cue indicative of sex and readily utilized in sex categorizations; Brown & Perrett, 1993;Goshen-Gottstein & Ganel, 2000) can automatically trigger category activation itself . Thus, the extraction of a mere perceptual cue is sufficient to activate a social category representation per se.…”
mentioning
confidence: 99%
“…Indeed many studies originally failed to find priming for unfamiliar (previously unseen) faces (Ellis, Young, & Flude, 1990). More recent work has found repetition priming for unfamiliar faces (Goshen-Gottstein & Ganel, 2000), albeit smaller in size than for familiar faces, one explanation of which is the rapid formation of presemantic, perceptual representations of faces (Martin & Greer, 2011). Such an explanation could not explain semantic priming for unfamiliar faces, however (when prime and probe are typically no more perceptually similar for primed than for unprimed conditions).…”
Section: Subliminal Priming Of Facesmentioning
confidence: 87%